From Inflammasome to Exosome—Does Extracellular Vesicle Secretion Constitute an Inflammasome-Dependent Immune Response? - Cypryk, Wojciech; Nyman, Tuula A.; Matikainen, Sampsa (Frontiers in Immunology, 2018)
Inflammasomes are intracellular protein complexes of pattern recognition receptors and caspase-1, with essential functions in regulating inflammatory responses of macrophages and dendritic cells. The primary role of inflammasomes is to catalyze processing and secretion of pro-inflammatory cytokines IL-1β and IL-18. Recently, intracellular non-canonical inflammasome activation by caspases-4/5, which are also regulators of pyroptosis via processing gasdermin D, has been elucidated. Caspase-1, the effector protease of inflammasome complex, is also known to modulate secretion of large number of other proteins. Thereby, besides its known role in processing pro-inflammatory cytokines, the inflammasome turns into a universal regulator of protein secretion, which allows the danger-exposed cells to release various proteins in order to alert and guide neighboring cells. Majority of these proteins are not secreted through the conventional ER-Golgi secretory pathway. Instead, they are segregated in membrane-enclosed compartment and secreted in nanosized extracellular vesicles, which protect their cargo and guide it for delivery. Growing evidence indicates that inflammasome activity correlates with enhanced secretion of extracellular vesicles and modulation of their protein cargo. This inflammasome-driven unconventional, vesicle-mediated secretion of multitude of immunoregulatory proteins may constitute a novel paradigm in inflammatory responses. In this mini review we discuss the current knowledge and highlight unsolved questions about metabolic processes, signals, and mechanisms linking inflammasome activity with regulated extracellular vesicle secretion of proteins. Further investigations on this relationship may in the future help understanding the significance of extracellular vesicle secretion in inflammatory diseases such as atherosclerosis, gouty arthritis, asthma, Alzheimer’s and many others.